Presence of double stranded RNA in natural isolates of Pycnoporus cinnabarinus - V. CIFUENTES; C. Martinez; G. Pincheira (Fungal Genetics Reports, 1990)
While studying the nucleic acids of different strains of P. cinnabarinus (Pc58, Pc470.3, Pc470.6), the presence of dsRNA molecules (1.7 kb to 3.6 kb) was detected in two of them.